THE IMPORTANCE AND HIDDEN RESOURCES OF LIFELONG LEARNING - Mátyás, Imre (European Integration Studies, 2015)
Lifelong learning is one of the key words of the 21st century. It seems to be essential not only in the western countries but also in the developing economies. On the one hand, in the ever changing surrounding of the welfare societies, it is important to provide the population the chance to acquire competitive knowledge that can make them suitable for the challenging of the market economy. On the other, it is also of crucial importance in the developing countries to provide not only general education for the youth but also further tuition for the adults. Thus, lifelong learning is a worldwide need of our age. It can be found in the core of the aims of different international organizations, for example the World Education Forum that put it directly in the headline among four other targets (These are: equity, inclusion, learning, quality, and lifelong learning.) How did the education develop? What is the exact definition of lifelong learning? Why is it so important? What advantages can be expected in the societies at different economic levels? What is a learning society? These questions are dealt with in the paper.